PENERAPAN PASAL (4) PP NO 21 TAHUN 2020 DI LINGKUNGAN RT.05/RW.15 BANTARJATI BOGOR UTARA - Zulhusni, Ridzki Nugraha; Bhudiman, Budy; Ratnawaty, Latifah (Universitas Ibn Khaldun Bogor, 2021)
In the context of efforts to tackle the COVID-19 pandemic, the government enforces a public health emergency which is carried out by implementing health quarantine as stipulated in Law Number 6 of 2018 concerning Health Quarantine. The spread of Corona Virus Disease 2019 (COVID-19) in Indonesia is currently increasing and expanding across regions and countries accompanied by a high number of cases and/or the number of deaths. This increase has an impact on the religious, educational, and public facilities provided by the government, so it is necessary to accelerate the handling of Covid-19 which is carried out in the form of Large-Scale Social Restriction measures to reduce the spread of Covid-19 increasingly widespread as stated in PP NO. 21 of 2020. These measures include restrictions on certain activities of residents in an area suspected of being infected with Covid-19, including restrictions on the movement of people and/or goods for a particular province or district/city to prevent the spread of Covid-19. This paper aims to examine how the implementation of large-scale social restrictions (PSBB) following article (4) PP NO. 21 of 2020 within the scope of RT.05 / RW.15 Bantarjati, North Bogor. AbstrakDalam rangka upaya penanggulangan pandemi COVID-19 pemerintah memberlakukan darurat kesehatan masyarakat yang dilakukan dengan penyelenggaraan kekarantinaan kesehatan sebagaimana telah diatur dalam Undang-undang Nomor 6 Tahun 2018 tentang Kekarantinaan Kesehatan. Penyebaran Corona Virus Disease 2019 (COVID-19) di Indonesia saat ini sudah semakin meningkat dan meluas lintas wilayah dan lintas negara yang diiringi dengan jumlah kasus dan/atau jumlah kematian yang tinggi. Peningkatan tersebut berdampak pada aspek keagamaan, pendidikan, serta fasilitas umum yang disediakan pemerintah, sehingga diperlukan percepatan dalam penanganan Covid-19 yang dilakukan dengan bentuk tindakan Pembatasan Sosial Berskala Besar dalam rangka menekan penyebaran Covid-19 semakin meluas yang tertuang pada PP NO. 21 Tahun 2020. Tindakan tersebut meliputi pembatasan kegiatan tertentu penduduk dalam suatu wilayah yang diduga terinfeksi Covid-19 termasuk pembatasan terhadap pergerakan orang dan/atau barang untuk satu provinsi atau kabupaten/kota tertentu untuk mencegah penyebaran Covid-19. Tulisan ini bertujuan untuk mengkaji bagaimana penerapan Pembatasan Sosial berskala Besar (PSBB) sesuai dengan pasal (4) PP NO. 21 Tahun 2020 di dalam ruang lingkup RT.05/RW.15 Bantarjati Bogor Utara.